Big Data Analysis of a Dedicated YouTube Channel as an Open Educational Resource in Hand Surgery - Rahman, Norana Abdul; Ng, Hannah Jia Hui; Rajaratnam, Vaikunthan (Frontiers in Applied Mathematics and Statistics, 2021)
Background Educationally designed videos have the advantage of explaining difficult concepts via graphic diagrams and dynamic illustrations. The benefits of videos will be enhanced if videos are well-designed, concise, explore scientifically correct content and have clear presentation. Aims Videos as an open educational resource (OER) is the corner stone for online learning. YouTube has been widely used as a distribution platform for OER. The aim of this study was to evaluate the engagement of hand surgery videos on a dedicated education channel on YouTube. Methods The author has been utilising a YouTube channel dedicated to the education of clinicians in Hand Surgery, surgical education and management since 2008. The degree of engagement was evaluated using YouTube Analytics, providing up-to-date metrics and reports. Results Since 2008, there has been 6521 subscribers with 1,360,680 views and with total view time of 35,033 hours and an average view time of 1.72 minutes. The channel views averaged 1000 views per day. There were 4,324,724 impressions with a 7.32% click through rate with United States of America accounting for 23.5% of the audience .YouTube search accounted for 33.3% of the traffic source and suggested videos by others was 19.4% and external links was 19%. Playback location was through mobile devices in 76.7%, whilst 16% was through the computer. The 2 popular playlists were “flaps in hand surgery” (50.2%) and “basic hand surgery workshop” (21.9%) . Sharing was by WhatsApp was most popular (27.9%) in embedded websites and apps. Overall there were 488 comments on the channel. Conclusion This paper confirms the phenomenon of micro-learning by online learners. It is recommended that educational videos as OER should be confined to 2 minutes, made compatible for mobile device, and be optimised for sharing on social media. These can be used as resources for blended learning, allowing better utilization of time for deliberate practice in surgical training.